2016
DOI: 10.1111/and.12697
|View full text |Cite
|
Sign up to set email alerts
|

Protective role ofAloe veraagainst X-ray induced testicular dysfunction

Abstract: The present investigation was carried out to evaluate the possible radioprotective potential of an Aloe vera extract against whole-body X-ray irradiation-induced testicular alterations in mice. Male balb/c mice were divided into four groups: control, A. vera, X-ray and A. vera pre-treated + X-ray irradiated. Histopathological examination revealed significant structural alterations in testes after X-ray exposure, which was also associated with the presence of apoptotic cells as assessed by TUNEL assay. X-ray ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
4
17
0
Order By: Relevance
“…Previously, we have reported that the apoptotic index was increased in testes of X-ray irradiated mice, which was decreased upon A. vera gel extract administration. 30 The alterations in hematological parameters are considered the most sensitive biological markers for the exposure to both internal and external irradiation. After whole-body gamma irradiation, injury to animal tissues was well reflected in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have reported that the apoptotic index was increased in testes of X-ray irradiated mice, which was decreased upon A. vera gel extract administration. 30 The alterations in hematological parameters are considered the most sensitive biological markers for the exposure to both internal and external irradiation. After whole-body gamma irradiation, injury to animal tissues was well reflected in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…These animals were exposed to a cumulative dose of 2 Gy (0.258 Gy twice a day for 4 days in the last week) and the dose of X-ray was standardized in the Department of Radiodiagnosis and Imaging, PGIMER, Chandigarh. 30,31 Animal treatment and study design Male balb/c mice (25-30 g) were selected from an inbred colony of central animal house, Panjab University (Chandigarh) maintained under the controlled conditions of temperature (23 + 2 C), humidity (50 + 5%), and 12 h of light and dark cycle, respectively. The animals were provided with a standard pellet diet as recommended by the Ashirwad Industries Ltd., Ropar, Punjab (India) and water ad libitum.…”
Section: A Vera Gel Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bala et al [12] evaluated the possible radio-protective potential of aloe vera extract against whole-body X-ray irradiation-induced testicular alterations in male balb/c mice. X-ray irradiation resulted in elevation of the levels of reactive oxygen species, lipid peroxidation, a reduction in glutathione concentration, but interestingly, enhanced activities of antioxidant enzymes such as glutathione reductase, glutathione peroxidase, catalase, SOD and glutathione-S-transferase.…”
Section: Wide Benefits Of Aloe Vera and Its Ingredientsmentioning
confidence: 99%
“…Administration of Aloe vera extract provided protection against radiation induced testicular damage in mice by its ability to scavenge free radicals and strengthen the cellular anti-oxidant defense system. 158 , 159 Withania somnifera has the ability to mitigate arsenic induced toxicity in rats. 160 Several researchers have investigated the anticancer effects of Withania somnifera against skin, prostate, colon, leukemia etc in animal models and cell lines.…”
Section: Growing Prospects Of Botanicalsmentioning
confidence: 99%